Predictive modeling for non-performing assets in the indian banking sector (Journal of Statistical Research, 2025)
This paper explores the financial and operational factors that contribute to India’s Nonperforming Assets (NPA) problem and discusses practical solutions for mitigating the risk of future NPAs. Descriptive statistics, regression analysis, and time series analysis are used to identify the main drivers of NPAs of Indian banks, revealing that high levels of NPAs have resulted in lower profitability, increased provisioning requirements, and higher borrowing costs. The findings and recommendations of this study provide valuable insights for policymakers, regulators, and banking practitioners seeking to reduce the risk of NPAs in India.Journal of Statistical Research 2024, Vol. 58, No. 2, pp. 335-351